2020
DOI: 10.3390/polym12123056
|View full text |Cite
|
Sign up to set email alerts
|

The Study of Physico-Mechanical Properties of Polylactide Composites with Different Level of Infill Produced by the FDM Method

Abstract: The aim of this study was to evaluate the changes in physical-mechanical properties of the samples manufactured by 3D printing technology with the addition of varying degrees of polylactide (PLA) infill (50, 70, 85 and 100%). Half of the samples were soaked in physiological saline. The material used for the study was neat PLA, which was examined in terms of hydrolytic degradation, crystallization, mechanical strength, variability of properties at elevated temperatures, and dissipation of mechanical energy depe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 49 publications
0
12
0
Order By: Relevance
“…As was showed in previous work [ 6 ], the infill density directly affects the mechanical properties. Rahmatabadi et al also showed this dependence.…”
Section: Introductionmentioning
confidence: 59%
See 2 more Smart Citations
“…As was showed in previous work [ 6 ], the infill density directly affects the mechanical properties. Rahmatabadi et al also showed this dependence.…”
Section: Introductionmentioning
confidence: 59%
“…Fan speed was 20% and the retraction distance was 0.8 mm. According to the properties of polylactide based on DSC research, the temperature of extrusion was 190 °C [ 6 ]. To ensure the proper adhesion of the material the applied heating of the table amounted to 50 °C.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Higher infill densities, such as 100%, led to increased crystallinity compared to lower infill densities . This effect can be attributed to the denser infill structure, which facilitates improved molecular alignment and promotes more efficient nucleation and crystallization . Additionally, the choice of the infill pattern played a crucial role in determining crystallinity.…”
Section: Resultsmentioning
confidence: 99%
“…In the early 1990s, the inventor Stratasys developed a new method for additive manufacturing or 3D printing: Fused Filament Fabrication (FFF) or Fused Deposition Modelling (FDM). FDM technology is based on the creation of parts from the deposition of layers of extruded thermoplastic material on a heated platform [ 3 , 4 ]. It is currently the most widely used additive manufacturing process and is present in a wide range of sectors.…”
Section: Introductionmentioning
confidence: 99%